Alpha‐Synuclein Dopaminylation Presented in Plasma of Both Healthy Subjects and Parkinson's Disease Patients. Issue 5 (12th July 2020) - Zhao, Huiyuan; Huang, Shuai; Palanisamy, Sivakumar; Wang, Cui; Rainer, Gregor; Zhang, Xiaozhe
Abstract : Purpose: Alpha‐synuclein (α‐syn) dopaminylation can lead to the death of dopaminergic neurons in the brain and is a risk factor of Parkinson's disease (PD). This study aims to examine whether such a posttranslational modification (PTM) is presented in human blood plasma. Experimental Design: In vitro reaction simulation between α‐syn and dopamine (DA) is conducted to study the biochemical mechanism. Then α‐syn from human blood plasma samples is detected by using immunoprecipitation‐mass spectrometry (IP‐MS). Lastly the levels of endogenous α‐syn and α‐syn dopaminylation in 88 blood plasma samples from patients with PD, major depressive disorder (MDD), and healthy control (HC) are compared. Results: DA modifies α‐syn with the addition of dopamine‐quinone (DAQ) into lysine sites of α‐syn in vitro and the addition of DAQ and 3, 4‐dihydroxyphenylacetaldehyde (DOPAL) in plasma samples. The unmodified α‐syn between the PD and HC groups showed similar levels. The levels of two peptides, one with lysine 34 ( 34 K) DAQ modification and the other with lysine 23 ( 23 K) ubiquitination, are significantly higher in PD and MDD compared with HC. Conclusions and Clinical Relevance: Thus, α‐syn dopaminylation is measurable and might be used to indicatethe presence and progression of neurological disorders.